2007
DOI: 10.1007/s10549-007-9747-9
|View full text |Cite
|
Sign up to set email alerts
|

Favourable long-term results after surgical removal of lung metastases of breast cancer

Abstract: We retrospectively evaluated whether a surgical strategy benefits patients with operable lung metastasis of breast cancer. Between 1960 and 2000, 90 patients (mean age 55.1; range 32-77) with lung metastasis (79 solitary, 11 multiple) underwent surgery as follows: wedge resection (n = 10), segmental resection (n = 11), lobectomy (n = 68) and pneumonectomy (n = 1). The metastases were completely resected in 89% of them. One patient died due to surgical complications. The overall 5- and 10-year cumulative overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
2
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 13 publications
5
46
2
10
Order By: Relevance
“…The literature search performed on 15 February 2017 had 2426 hits in MEDLINE and found one review article in the Cochrane library. After step-wise appraisal 11 studies where identified each with at least 20 patients having had lung metastasectomy following primary tumour treatment with curative intent [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature search performed on 15 February 2017 had 2426 hits in MEDLINE and found one review article in the Cochrane library. After step-wise appraisal 11 studies where identified each with at least 20 patients having had lung metastasectomy following primary tumour treatment with curative intent [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Methodsmentioning
confidence: 99%
“…Ten of the reviewed studies were case series, together reporting on over 971 patients with treated breast carcinoma and pulmonary metastasectomy [2][3][4][5][6][7][8][9][10][11]. Operations were performed between 1960 and 2007.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations